1992
DOI: 10.1007/bf00243518
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ventilation in response to ramp changes in treadmill exercise load

Abstract: These experiments examined the changes in ventilation during a 40-s ramp increase in exercise load, produced by increasing either the speed of the treadmill or the grade, to equivalent end-points of oxygen uptake. Six subjects underwent five trials each for grade and speed, while ventilation was monitored breath-by-breath. For each subject, ventilation versus time for all five of the speed trials was plotted on a single graph and fitted by linear regression. The data for the grade trials were similarly treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Moreover several investigators have found that for the same increase in metabolic rate, the tachypnea and hyperpnea are greater when the treadmill speed or cycling frequency is increased as opposed to an increase in treadmill grade or cycling resistance (5,32,53,67,179,193,194,242). Furthermore during sinusoidal changes in work rate, investigators have found greater amplitudes and lower phase lags for ventilation when limbmovement frequency is varied compared to variations in treadmill grade or cycle resistance (64,65,342).…”
Section: Breathing Frequency and Limb-movement Frequencymentioning
confidence: 92%
“…Moreover several investigators have found that for the same increase in metabolic rate, the tachypnea and hyperpnea are greater when the treadmill speed or cycling frequency is increased as opposed to an increase in treadmill grade or cycling resistance (5,32,53,67,179,193,194,242). Furthermore during sinusoidal changes in work rate, investigators have found greater amplitudes and lower phase lags for ventilation when limbmovement frequency is varied compared to variations in treadmill grade or cycle resistance (64,65,342).…”
Section: Breathing Frequency and Limb-movement Frequencymentioning
confidence: 92%
“…Thus, phase I ventilatory response might be regulated so that it is always maintained in the same in individual. On the other hand, some researchers have revealed that initial exercise hyperpnea is changed by various factors such as muscle pain and limb frequency (Kelsey and Duffin, 1992;Cerretelli et al, 1995;Hotta et al, 2006Hotta et al, , 2007aWells et al, 2007). Further study will be needed to clarify this contradiction.…”
Section: The Effect Of Increase In Imp On Phase I Ventilatory Responsementioning
confidence: 98%
“…Thus, an increase in exercise intensity or workload is expected to augment both central command and feedback signals from the exercising muscles, resulting in an exaggerated initial exercise hyperpnea. However, it has been well documented that phase I ventilatory response is unaffected by the alteration of exercise intensity or workload (Kelsey and Duffin, 1992;Cerretelli et al, 1995;Wells et al, 2007).…”
Section: The Effect Of Increase In Imp On Phase I Ventilatory Responsementioning
confidence: 99%
See 1 more Smart Citation
“…For example, in treadmill walking, the incline of the treadmill can be paired with different treadmill speeds so that subjects walk with the same oxygen consumption at very different rates of limb movement. In all cases, the magnitude of the initial increase in ventilation (i.e., breath-by-breath measures of l/min) was associated with the rate of the movement rather than the load (Casey et al 1987;Duffin and Bechbache 1983;Kelsey and Duffin 1992;Wells et al 2007). Other studies in which the load of the movement (bicycling) is changed without a change in the rate of the movement also indicate that there is no rapid change in the minute ventilation when the load is altered (e.g., Whipp et al 1982).…”
Section: Rate Of Breathing Is a Function Of The Rate Of Steppingmentioning
confidence: 99%